Trimetazidine in Chronic Coronary Syndrome and Coronary Artery Disease: A Narrative Review of Clinical Efficacy, Safety, and Current Guideline Position - Daniel Miron Brie; Cristian Mornoș; Alexandru Tîrziu; Roxana Popescu; Alina Diduța Brie (Pharmaceuticals, 2026)
Background: Chronic coronary syndrome (CCS) is a major source of morbidity and healthcare utilization, and a substantial proportion of patients continue to experience angina despite contemporary revascularization and guideline-directed medical therapy. Trimetazidine, a metabolic anti-ischemic agent that does not affect heart rate or blood pressure, has been used for decades as a non-hemodynamic add-on. Its position in international guidelines, however, has shifted. We aimed to synthesize current evidence on the clinical efficacy, safety, and guideline status of trimetazidine in CCS and coronary artery disease (CAD) and to delineate clinical circumstances in which a symptom-directed trial may be considered. Methods: We performed a structured narrative review of randomized controlled trials, network and conventional meta-analyses, and large observational studies indexed in PubMed/MEDLINE, Embase, and the Cochrane Library between January 1990 and March 2026. Reference lists of eligible articles, international clinical practice guidelines, and regulatory communications from European and national agencies were also examined. Results: Across pooled analyses, trimetazidine modestly but reproducibly improved exercise tolerance and reduced angina frequency and short-acting nitrate use, with efficacy comparable to other non–heart-rate-lowering antianginal agents. Improvements in left ventricular function were reported in small, single-center studies in ischemic cardiomyopathy and selected high-risk subgroups; however, these findings have not been validated in contemporary large-scale trials, and their clinical significance against modern guideline-directed therapy is unknown. The ATPCI trial confirmed safety but showed no reduction in major adverse cardiovascular events after percutaneous coronary intervention. Rare extrapyramidal effects prompted the 2012 European Medicines Agency referral and several prescribing restrictions. Conclusions: Trimetazidine remains a reasonable symptom-directed adjunct for residual angina in carefully selected CCS patients, particularly those in whom further hemodynamic up-titration is limited or poorly tolerated. The 2024 ESC class IIb recommendation may partly reflect a broader emphasis on prognostic benefit, although the neutral post-PCI outcome evidence and regulatory safety restrictions also support a more cautious position.